Effect of solid-state fermentation and ultrasonication processes on antimicrobial and antioxidant properties of algae extracts - Tolpeznikaite, Ernesta; Starkute, Vytaute; Zokaityte, Egle; Ruzauskas, Modestas; Pilkaityte, Renata; Viskelis, Pranas; Urbonaviciene, Dalia; Ruibys, Romas; Rocha, João M.; Bartkiene, Elena (Frontiers in Nutrition, 2022)
The aim of this study was to evaluate the influence of solid-state fermentation (SSF) on Lactiplantibacillus plantarum LUHS135 and ultrasonication (45 min, 35 kHz) of macroalgae (Cladophora rupestris, Cladophora glomerata, Furcellaria lumbricalis, Ulva intestinalis) and microalgae (Spirulina (Arthrospira platensis)) extracts. Combinations of extract × pure LUHS135 were developed and their antioxidant and antimicrobial characteristics were evaluated. It was found that the species of algae is a significant factor in the pH of samples (p = 0.017). The highest 2,2-diphenyl-1-picryhydrazyl (DPPH) radical scavenging activity and 2, 2′-azino-bis ethylbenzthiazoline-6-sulfonic acid (ABTS) radical cation scavenging were from C. rupestris and F. lumbricalis extract × LUHS135 combinations (on average, 1.86 and 4.63, 1.18 and 4.56, 1.54 and 5.20 µmol TE/mL, respectively). The highest ferric reducing antioxidant power (FRAP) was shown by non-pretreated C. rupestris and F. lumbricalis extract × LUHS135 combinations (on average, 2.19 and 2.37 µmol TE/mL, respectively). Moderate positive correlations between samples’ total phenolic compound (TPC) and ABTS (r = 0.300, p = 0.004) and FRAP (r = 0.247, p = 0.019) were established. An ultrasonicated samples showed inhibition properties against Bacillus cereus, Enterococcus faecium, Staphylococcus aureus and Streptococcus mutans strains. The data presented here show that extract combinations with LUHS135 have prospective results.